Perilaku Gaya Pacaran Berisiko Mahasiswa Universitas Islam Negeri Sumatera Utara - Dewi Harahap, Rosmala; Anggraini Siregar, Widya; Warda Situmorang, Fahita; Ayu Rahmadhani, Fitri (Cindoku : Jurnal Keperawatan dan Ilmu Kesehatan, 2025)
This study aims to understand the meanings and subjective experiences of students related to risky dating styles at the State Islamic University of North Sumatra (UINSU). The phenomenon of premarital sexual behavior and intensive dating styles was the focus of this research, considering the rising numbers of sexually transmitted infections and unintended pregnancies among adolescents and university students. A qualitative descriptive method was used, with in-depth interviews conducted with nine respondents. The results indicate that risky dating styles are influenced by factors such as low self-control, exposure to pornography, peer pressure, parenting patterns, religious values, and social media. Several respondents acknowledged that poor communication, jealousy, and pressure from partners negatively impacted their mental health, social relationships, and academic performance. Conversely, respondents with strong self-control and firm personal values tended to foster healthier and more respectful relationships. The conclusion emphasizes that self-control, open communication, and understanding of personal values are key elements in forming healthy dating relationships. These findings can serve as a basis for formulating sexual education strategies, campus-based interventions, and preventive policies to create a conducive and respectful academic environment.